Restless leaf rust - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
For the first time since it was introduced in Nigeria almost one hundred years ago, soybean cultivation in Nigeria has been seriously hit by a leaf rust disease, this time caused by the fungus Phakospora pachyrhizi. Losses in the south-western...